2016
DOI: 10.1089/end.2016.0129
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral Stent-Associated Pain: A Review

Abstract: Ureteral stent pain is common and multiple modalities have been studied and are in clinical use for its treatment. Care should be taken to avoid placement of stents if possible, with continual reassessment of indications to maintain stents in patients. Relative heterogeneity among studies and small sample sizes make creating specific evidence-based pain management recommendations challenging. Alpha-blockers, antimuscarinics, and NSAIDs are all generally well tolerated and effectively reduce symptoms, but patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 56 publications
1
34
1
1
Order By: Relevance
“…Up to 80% of patients with indwelling stents experience pain, lower urinary tract symptoms (LUTSs), or both, resulting in a significant impact on their quality of life (QoL). [1][2][3][4][5][6] Some of these symptoms are associated with an incorrect choice of stent length for a given patient. 4,5,7 Multiple studies and a recent review 6 have shown that stents that are too long, especially when the distal coil crosses the midline, are associated with more dysuria, urgency, and frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Up to 80% of patients with indwelling stents experience pain, lower urinary tract symptoms (LUTSs), or both, resulting in a significant impact on their quality of life (QoL). [1][2][3][4][5][6] Some of these symptoms are associated with an incorrect choice of stent length for a given patient. 4,5,7 Multiple studies and a recent review 6 have shown that stents that are too long, especially when the distal coil crosses the midline, are associated with more dysuria, urgency, and frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Although known and established for decades, the exact pathophysiology of SRS remains unknown. Several conflicting theories have been proposed, attributing SRS to the distal end of the stent that lies in the bladder causing trigonal bladder mucosa irritation, smooth muscle spasm, and/or inflammatory reaction of the ureter and bladder, or a combination of factors [16,17]. Given that a stent should be in place, and this premises its proper and judicious use, urologists have to adopt strategies in order to relieve SRS.…”
Section: Discussionmentioning
confidence: 99%
“…α 1adrenoceptors have been found in the human distal ureter and their blockage results in basal tone and ureteric peristaltic frequency inhibition, and consequently in ureteric lumen dilatation and spasms reduction [20]. In addition, the relaxation of the bladder neck and prostatic smooth muscle leading to voiding pressure and urinary reflux reduction, may explain the decrease in pain noticed during voiding [17,21]. Differences noticed between α-blockers regarding their effectiveness on SRS and side-effects are conflicting and considered not significant.…”
Section: Discussionmentioning
confidence: 99%
“…These SRS range from bladder/flank pain to storage symptoms to hematuria. Although the underlying pathophysiology behind these complaints are not yet fully elucidated, bladder wall and trigonal irritation by the distal coil as well as vesicoureteral reflux and retrograde pressure transmission have been proposed as underlying mechanisms [32] , [33] . Apart from being bothersome for the patient, stent-related symptoms can also lead to socio-economic burden.…”
Section: Stent-related Complicationsmentioning
confidence: 99%